2005
DOI: 10.1021/bp0400339
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Saccharification and Co‐Fermentation of Crystalline Cellulose and Sugar Cane Bagasse Hemicellulose Hydrolysate to Lactate by a Thermotolerant Acidophilic Bacillus sp.

Abstract: Polylactides produced from renewable feedstocks, such as corn starch, are being developed as alternatives to plastics derived from petroleum. In addition to corn, other less expensive biomass resources can be readily converted to component sugars (glucose, xylose, etc.) by enzyme and/or chemical treatment for fermentation to optically pure lactic acid to reduce the cost of lactic acid. Lactic acid bacteria used by the industry lack the ability to ferment pentoses (hemicellulose-derived xylose and arabinose), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 37 publications
1
51
0
2
Order By: Relevance
“…It has been reported that acidic pH induces the production of cellulases in thermophilic cellulolytic Bacillus sp. (Patel et al 2005). The high tolerance of this strain to acidic pH suggests that it has the potential for use in the harsh environments encountered during industrial fermentation.…”
Section: Effect Of Ph On Cellulase Productionmentioning
confidence: 96%
“…It has been reported that acidic pH induces the production of cellulases in thermophilic cellulolytic Bacillus sp. (Patel et al 2005). The high tolerance of this strain to acidic pH suggests that it has the potential for use in the harsh environments encountered during industrial fermentation.…”
Section: Effect Of Ph On Cellulase Productionmentioning
confidence: 96%
“…Use of the hemicellulolytic organisms alone at high temperatures could potentially lower the quantity of added cellulase required. For example, Patel et al (11) report lactic acid production from cellulose at low cellulase loadings, by using a thermophilic Bacillus species. T. saccharolyticum JW/SL-YS485 is one such hemicellulolytic organism with the ability to hydrolyze xylan and ferment the majority of biomass-derived sugars at thermophilic temperatures.…”
mentioning
confidence: 99%
“…With cellulose as a feedstock, however, commercial fungal cellulases represent a significant process cost. This cost could be reduced by the development of thermotolerant biocatalysts that effectively ferment under conditions that are optimal (pH 5.0, 50°C) for fungal cellulases (14,15).…”
mentioning
confidence: 99%